Saudi Arabia and Iran: the Battle for Hegemony That the Kingdom Cannot Win - Dorsey, James M. (Przegląd Strategiczny, 2016)
Challenged economically, politically, socially, ideologically and geopolitically, Saudi Arabia is confronting the perfect storm. How it weathers the storm will depend on how it handles the two most existential threats it faces: the rivalry with Iran for hegemony in the Middle East and North Africa (a battle it ultimately will lose), and the inevitable restructuring of the increasingly problematic marriage between the House o f Saud and the Wahhabi clergy, proponents of a puritan interpretation o f Islam on whom the ruling Al Saud family rely for their legitimacy.